A universal self‐eroding sacrificial bioink that enables bioprinting at room temperature. (20th March 2020) - Aydin, Levent; Kucuk, Serdar; Kenar, Halime
Abstract : Natural polymer‐based hydrogel bioinks are widely used in bioprinting due to their suitability for recapitulation of in vivo cellular activities. However, preservation of the target geometry in a cell‐laden hydrogel is difficult to achieve. The aim of this study was to develop a universal sacrificial bioink that allows high cell viability and a better shape fidelity in the cell‐laden construct. A polysaccharide‐based universal sacrificial bioink was developed for microextrusion‐based bioprinting and was optimized to erode in 48 hours in the cell culture medium without formation of any undesired by‐products. The sacrificial hydrogel was prepared from alginate and agarose via a microwave oven assisted method and bioprinted at room temperature to generate microchannels in the cell‐laden hydrogel or to support a tubular structure and its biocompatibility determined by live/dead assay. Bioprinting time was significantly reduced, down to a few minutes for a large‐scale tissue model (1 minute 52 seconds for a 2 cm tubular structure), by means of a high bioprinting speed up to 25 mm/s. After 48 hours in the cell culture, the sacrificial bioink completely detached from the cell‐laden construct without causing any changes in its printed shape. Cell viability in the cell‐laden construct was observed to be more than 95% at the end of 3‐day culture. This novel sacrificial bioink enables bioprinting at room temperature without affecting oxygen and nutrient penetration into the cell‐laden hydrogel and allows retention of high cell viability and shape fidelity. Abstract :